Modelagem hidrossedimentológica para bacia do Alto Teles Pires - Lopes, Tárcio Rocha (2016)
In recent years, several studies have been carried out in relation to land use change and land cover, covering several other areas, such as deforestation, expansion of agricultural frontiers, livestock and urbanization. The different scenarios and changes in land use generate impacts on hydrographic basins, mainly the decrease in evapotranspiration due to logging and increased surface runoff, which causes changes in flow rates, increase of events such as flooding, erosion and silting Water, which ultimately causes changes in the quantity and quality of water resources. In this context, hydrological modeling is an essential tool because it considers the spatial and temporal distribution of hydrological processes and can be used for several purposes, such as the forecast of short and medium term flow, availability of hydrological resources and hydrology variability as a consequence of Land use changes and land cover. The objective of this work was to calibrate, validate and evaluate the performance of the SWAT model applied to the Upper Teles Pires basin and later to verify the effect of changes in soil use and occupation on the components of the water balance and to analyze the quantification of the production of sediments. As input data for feeding the model, the Digital Elevation Model (DEM) with a resolution of 30m, maps with the soil types and use and soil cover were used, as well as the WXGEN model, available in SWAT, for the generation Of the daily data of temperature, relative humidity of the air, speed of the wind and solar radiation. In this work, calibration and validation were performed for daily and monthly levels of surface runoff at three fluviometric stations and their performance was verified according to statistical parameters. Four soil use and land use scenarios were used: 1986, 1996, 2006 and 2014, and its reflection on surface, lateral and subsurface runoff, evapotranspiration, water production and soil water content were verified. We performed the spatialization of the factors that make up the Modified Universal Soil Loss Equation (MUSLE), as well as the sediment production in the basin. Based on the statistical parameters, the SWAT was able to simulate the Upper Teles Pires River basin flows adequately. The model presented better simulation results for the calibration period than for the validation period and being better for basins with larger areas. Additionally it can be used for the study of alternatives of management / management of water resources under different scenarios of land use and occupation. The simulation of sediment yield in basin shows an average of 7.74 Mg ha-1 year-1 . The maps indicative of erosion susceptible parameters and the distribution of sediment yield to basin indicate the decision to take conservation measures to control erosion.